A comparison of the effects of mangrove ecosystems (disturbed and undisturbed) on the populations of birds and fishes at Hope Beach, East Coast Demerara, region 4, Guyana - Dookram, K.; Jaikishun, S.; Ansari, A. A.; Seecharran, D. (International Journal of Agricultural Technology, 2017)
Mangroves are very productive ecosystems that provide habitats and food to many terrestrial and aquatic organisms. However, humans constantly degrade mangroves for agricultural purposes, near shore mining, fishing, the construction of infrastructure and other activities, which destroy the habitats of many organisms. This study compared the population of birds and fishes in two mangrove sites that were categorized as disturbed and undisturbed. From the results obtained it was observed that the populations of birds and fishes were higher in the undisturbed compared to the disturbed. However, the disturbed site had a higher forest density. Moreover, the undisturbed site comprised of a mixed mangrove forest with three mangrove species, while the disturbed had one species. Further, this study emphasized how anthropogenic activities affect birds and fishes utilizing mangrove forests for survival. It was revealed that little to no disturbance in a mangrove forest encourages higher populations of living organisms particularly birds and fishes.